ANALISIS FAKTOR EKSTERNAL DAN INTERNAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK HAND SANITIZER DI MASA PANDEMI COVID-19 - Leo Alexander Tambunan (SIMAK, 2021)
The purpose of this study is to find out what factors influence consumer decisions to buy hand sanitizer products during covid-19. This research was conducted on 100 people who made purchases of hand sanitizers. This research belongs to the type of descriptive research with survey method. The data in this study were obtained through observation and questionnaires. The data analysis technique in this study used Partial Least Square (PLS). Several tests were carried out including: descriptive statistical test, Measurement Model Test or Outer Model, and Structural Model Test or Inner Model. Based on the results of the study, it was found that external factors did not have a significant influence on purchasing decisions as indicated by a significance value of 0.233>0.05. while internal factors have a significant influence on purchasing decisions as indicated by a significance value of 0.000 <0.05. And the results obtained that simultaneously external factors and internal factors have an influence on purchasing decisions.